Migration restrictions and long-term regional development: Evidence from large-scale expulsions of Germans after World War II - Michael Wyrwich (Friedrich Schiller University Jena, 2018)
Migration restrictions are a hotly debated topic in the current refugee crisis in Europe. This paper investigates the long-term effect of a restrictive migration policy on regional development. The analysis is based on the large-scale expulsion of Germans from Cen-tral and Eastern Europe after World War II (WWII). Expellees were not allowed to reset-tle in the French occupation zone in the first years after the War while there was no such legislation in the other occupation zones (U.S.; U.K; Soviet Union). The temporary migra-tion barrier had long-lasting consequences. In a nutshell, results of a Difference-in-Difference (DiD) analysis show that growth of population has been significantly lower in the long run, if a region was part of the French occupation zone. Even 60 years after the removal of the barrier the degree of agglomeration is still significantly lower in these areas. The paper discusses implications for the current refugee crisis.
Keywords: J11; J61; N34; R11; R23; 330; Migration barrier; population shock; refugee migration; long-term regional development